Respuesta :
Answer:
14x + 4
Step-by-step explanation:
3(4x+2) + 2(x-1)
Distribute by multiplying into the bracket
=12x + 6 + 2x - 2
Group like terms by adding and subtracting
= 14x + 4
Answer:
1) Multiply and expand the brackets:
12x + 6 + 2x - 2
2) Combine like terms (combine terms that have an x together, and those that don't together.)
14x + 4
If the question wanted you to simplify the expression, then 14x + 4 is your answer. However, to solve for x, you could equate the expression to 0, but I'm not too sure of this part.
14x + 4 = 0
14x = - 4
x = - 4/14
x = - 2/7